Multimedia Instruction & Language Learning Attitudes: A Study with University Students - Jesús Izquierdo; Daphnée Simard; María Guadalupe Garza Pulido (Revista Electrónica de Investigación Educativa)
This study examined the effects of two types of Multimedia Instruction (MI) and learners’ second language (L2) proficiency on language learning attitudes. During four weeks, university learners of French received MI on the distinctive use of the perfective and the imperfective past in one of the four following conditions: learners with low L2 proficiency level exposed to MI with (n=17) or without language awareness tasks (n=17), and learners with intermediate L2 proficiency level exposed to MI with (n=14) or without language awareness tasks (n=28). Before and after the experiment, participants completed the Attitude/Motivation Test Battery (AMTB). Non-parametric analyses revealed a positive enhancement of classroom-related attitudes only among intermediate learners exposed to MI without Language Awareness Tasks. Nevertheless, the results showed similar as well as stable attitudes towards language learning in all the experimental conditions.